Institutional arrangements for implementation of a municipal payment program for water environmental services: case study of Sao Jose dos Campos (SP) - Fiore, Fabiana Alves [UNESP]; Santos Bardini, Vivian Silveira dos [UNESP]; Pereira Cabral, Paula Cristina (Assoc Brasileira Engenharia Sanitaria Ambiental, 2020)
The use of economic instruments as inductors of environmental quality has gained worldwide prominence. In the last decade, Brazil experienced the implementation of Payment for Environmental Services (PES) programs to promote the restoration and conservation of natural resources, with recognized environmental gains. Considering the incipience of the use of this strategy as a municipal public policy, the present work was developed with the purpose of presenting the case study of the PES project in implantation in the municipality of Sao Jose dos Campos, in the Couves creek. The accomplishment of this research was subsidized by bibliographical revision, documental analysis and structured interviews, contemplating from its genesis, in 2010, until 2017. From the results, it was possible to verify that the municipal public agents invited efforts during the first five years to acquire knowledge, to establish regulatory means, to guarantee economic resources, to involve social agents affected by this policy, until it was possible to start the project During this period the institutional arrangement was established, motivated by the viability of learning of the partner entities and the opportunity of contribution and sharing. The main gains from the implementation of the project are related to the increase of native vegetation and the improvement of water quality in the watershed that are used as source for local public supply. Among the challenges highlighted by public managers is the inexistence of resources: human, material, and financial dedicated to the initiative. Finally, it is highlighted that the learning generated by the project will serve the municipality for the continuity of the program and similar projects.
Keywords: payment for environmental services; Sao Jose dos Campos; institutional arrangements